The X‐linked filaminopathies: Synergistic insights from clinical and molecular analysis. Issue 5 (11th March 2020) - Wade, Emma M.; Halliday, Benjamin J.; Jenkins, Zandra A.; O'Neill, Adam C.; Robertson, Stephen P.
Abstract: The X‐linked filaminopathies represent a diverse group of clinical conditions, all caused by variants in the gene FLNA. FLNA encodes the widely expressed actin binding protein, filamin A that has multiple roles during embryonic development including cell migration, mechanical sensing, and cell signaling. In this review, we discuss the 10 distinct X‐linked filaminopathy conditions that between them affect almost all organ systems, including the brain, skeleton, heart, and skin, highlighting the critical role of this protein in human development. We review each of the phenotypes and discuss their pathogenesis, where known. Assigning pathogenicity to variants in FLNA can prove difficult, especially for missense variants and small indels, in‐part because of the X‐linked nature of the phenotypes, the overlap of phenotypic features between conditions, and poor understanding of the function of certain protein domains. We outline here approaches to characterize phenotypes, highlight hotspot regions within FLNA commonly mutated in these conditions, and approaches to resolving some variants of uncertain significance. Abstract : The location of causative variants leading to the filaminopathies A are mapped onto FLNA protein monomers. Variants leading to 'loss‐of‐function' disorders (left monomer) and 'gain‐of‐function' disorders (right monomer) can clearly be seen to cluster. 'Hotspot' regions are marked with larger symbols. PH: periventricular heterotopia, CIPX: congenital intestinal pseudo‐obstruction, IMT: isolated macrothrombocytopenia, FCMPD: familial cardiac myxomatous polyvalvular dystrophy, OPD: otopalatodigital syndrome, FMD: frontometaphyseal dysplasia, CKCO: condition comprising contractures, keloid, cardiac defects and optic anomalies, MNS: Melnick‐Needles syndrome, DCD: digitocutaneous dysplasia, ABD: actin‐binding domain, CHD: calponin homology domain, H: hinge.